CHALLENGES TO DEMOCRATIC EQUALITY (CIPEEX, 2025)
The misuse of economic resources and political influence during election campaigns represents a major challenge for the integrity of our democratic process in Brazil. These practices harm equal opportunities among candidates, benefiting those who have more money or privileged access to the public machine. This work aims to analyze the impacts of the abuse of economic and political power in Brazilian elections and reflect on the actions taken by the Electoral Justice to combat these behaviors. For this, we conducted a specialized literature review and analyzed important judicial decisions issued by the Superior Electoral Court (TSE). The results clearly show that these attitudes harm the legitimacy of the vote, unbalance the dispute and undermine the population's confidence in the electoral system. Although there are legal mechanisms, such as specific lawsuits and rules that apply sanctions to candidates and parties, there are still difficulties in applying these punishments effectively. It is also important to note that, even with the action of the Electoral Justice to combat these abuses, it is necessary to implement more effective measures to ensure greater justice in the process. We conclude that facing the abuse of power in campaigns requires advances in legislation, stricter supervision and a political culture based on ethics, transparency and respect for democratic rules - all this to make our elections fairer and more representative.
Keywords: Abuse of power; Election campaigns; Oversight; Electoral Justice; Political financing